Implementation of ACR and AVR controls for high voltage gain DC-DC Converter - Jawher Al-Janabi, Omar Hameed (2019)
Step up power conversion is universally used in many applications. The application that uses step-up power conversion can be observed in renewable energy such as photovoltaic (PV) system, wind turbine, data center and Electric vehicle. There are many applications which use the DC-DC boost converter to get higher DC voltage from the low input voltage. In this project, Marx topology boost converter (MTBC) analyzed and proposed for conversion from low input dc voltage to high output dc voltage. (MTBC) depends on the principle of the Marx generator. The proposed (MTBC) is multi-stage and consist from 4-stage, by multistage of converter the stress in the components will be reduced, where the parallel charging at input side to reduce the current stress, and series discharging at output to reduce the voltage stress. The stress on the components of the converter will inversely proportional with a number of stages. By implementation of ACR and AVR combination with using PI control technique the output voltage can be controlled. Based on the simulation results the obtained output voltage 400V DC by boosting input voltage 48V DC and by using 4- stage proposed converter, but any drop in the value of input voltage will effect on the output voltage, so that when battery voltage drop to 40V the output will be 340V. After implementing the control system for the AVR and ACR and combine between them, it will be possible to obtain 400V from different value input voltage (40V, 45V, 55V), as well as for 450V and 500V output voltage.